Implementation Of Card Match Learning Media In Arabic Language Learning in Madrasah Tsanawiyah Mabdaul Ma’arif Jember - Fatullah, Iqbal; Faisal Nasar Bin Madi; Bambang Irawan (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
Index Card Match is a learning strategy where students match or look for pair cards containing questions and answers. The purpose of media index card match is to create an active and fun learning atmosphere. This media covers the cognitive aspects of students because the characteristics of Arabic subjects also include understanding the concept of the material and not just doing an application. This media has high flexibility because it is easy to apply to all subjects at the unit level of any institution. The focus of research discussed is the implementation of index card match learning strategies in Arabic subjects in class VII MTs Mabdaul Maarif for the 2023/2024 academic year. This research uses a qualitative descriptive approach with a type of case study research. A number of research data were collected using observation, interview and documentation techniques. The results of the data obtained were then analyzed using interactive model analysis techniques from Miles & Huberman and Saldana. The validity of the data is obtained through two triangulation techniques, namely triangulation techniques and source triangulation. This study resulted in the conclusion that the implementation of the index card match learning strategy was carried out with three activity steps, namely initial activities, core activities, and closing activities.